2014
DOI: 10.1155/2014/614808
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Activity Relationship Study of Antitubercular Carboxamides

Abstract: The unusual structure and chemical composition of the mycobacterial cell wall, the tedious duration of therapy, and resistance developed by the microorganism have made the recurrence of the disease multidrug resistance and extensive or extreme drug resistance. The prevalence of tuberculosis in synergy with HIV/AIDS epidemic augments the risk of developing the disease by 100-fold. The need to synthesize new drugs that will shorten the total duration of effective treatment and/or significantly reduce the dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Carboxamides are ubiquitous in their function in drug molecules as a pharmacophore (Montalbetti and Falque, 2005). Carboxamides have been reported as antihelmintic (Ugwu et al, 2018a), antitubercular (Ugwu et al, 2014) anti-trypanosomal (Ugwu et al, 2018b) agents. They are also present in drug molecules used in the blockage of cholesterol synthesis (Graul and Castaner, 1997), treatment of hypertension and andina (Ananthanarayanan et al, 1993), blockade of angiotensin-II receptors (deGasparo and Whitebread, 1995), inhibition of angiotensin converting enzymes (Patchett, 1993), treatment of HIV (Roskoski, 2003), and management of heart disease (Hogan et al, 2000), to mention but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxamides are ubiquitous in their function in drug molecules as a pharmacophore (Montalbetti and Falque, 2005). Carboxamides have been reported as antihelmintic (Ugwu et al, 2018a), antitubercular (Ugwu et al, 2014) anti-trypanosomal (Ugwu et al, 2018b) agents. They are also present in drug molecules used in the blockage of cholesterol synthesis (Graul and Castaner, 1997), treatment of hypertension and andina (Ananthanarayanan et al, 1993), blockade of angiotensin-II receptors (deGasparo and Whitebread, 1995), inhibition of angiotensin converting enzymes (Patchett, 1993), treatment of HIV (Roskoski, 2003), and management of heart disease (Hogan et al, 2000), to mention but a few.…”
Section: Introductionmentioning
confidence: 99%
“…They have reported the inhibitory properties of these compounds towards Mycobacteria at concentrations of 50-100 µg/ml. Ugwu et al have also shown that the inhibitory concentrations of carboxamides against MT is in the range of 25-50 µg/ml [23] . Cho et al showed that the inhibitory concentrations of EGCG against the antibiotic resistant Imipenem Klebsiella pneumonia strains to be in the range of 300-650 µg/ml [12] .…”
Section: Resultsmentioning
confidence: 97%
“…Appropriate substituted benzenesulfonyl chloride (1ac, 1.82 mmol) was added in portions for 1 h to an aqueous solution of L-leucine (1.5 mmol) containing sodium carbonate (Na 2 CO 3 , 1.82 mmol) at −5 • C. The slurry formed was stirred at room temperature for 4 h (TLC (MeOH/DCM, 1:9 monitored). The mixture was acidified to pH 2 (Ugwu et al, 2014;Ezugwu et al, 2020).…”
Section: General Procedures For the Synthesis Of Substituted Benzenesumentioning
confidence: 99%
“…Carboxamides are also ubiquitous functionality GRAPHICAL ABSTRACT | in medicate particles as pharmacophores (Montalbetti and Falque, 2005). Carboxamides have been accounted for as antimicrobial and antioxidant (Eze et al, 2019), carbonic anhydrase enzyme inhibitor and antioxidant (Deniz et al, 2019), anticancer (Kumar et al, 2009), anthelmintic (Ugwu et al, 2018a), antitubercular (Ugwu et al, 2014), antitrypanosomal (Ugwu et al, 2018b), and anti-inflammatory and analgesic (Ugwu et al, 2018c) agents. Day and Greenfield (2004) reported that peptides are resourceful pharmacophores as they play important roles within the physical body and other organisms.…”
Section: Introductionmentioning
confidence: 99%